Lifestyle, psychological stress, and incidence of adolescent constipation: results from the Toyama birth cohort study - Masaaki Yamada; Michikazu Sekine; Takashi Tatsuse; Yuko Fujimura (BMC, 2021)
Abstract Background We aimed to clarify the predisposing factors for adolescent constipation in a longitudinal study, because while factors associated with childhood constipation have been reported, prospective studies on the incidence of constipation are lacking. Methods We enrolled 5540 adolescents aged 12 to 13 years from the Toyama Birth Cohort Study-a community-based prospective study examining children's health. The incidence of constipation, defined as bowel movement frequency of less than once every 2 days, was surveyed during the three-year period from baseline (grade 4) to follow-up (grade 7). Multivariate logistic regression analyses were performed to explore the association between the incidence of adolescent constipation and their lifestyle variables. Results A total of 261 adolescents (4.7%) developed constipation during the three-year period. Female sex (odds ratio [OR] = 2.62,) overweight (OR = 0.60), and infrequent intake of fruits (OR = 1.50) at baseline were associated with the incidence of constipation. Furthermore, factors related to lifestyle changes and psychological status such as skipping breakfast (OR = 1.73), becoming physically inactive (OR = 1.55), and being persistently irritated (OR = 1.80) were significantly associated with the incidence of constipation. Conclusion Our prospective study demonstrated that female sex, insufficient fruit intake, and deteriorating lifestyles such as skipping breakfast and becoming inactive during the 3-year period were associated with the incidence of adolescent constipation. Beyond anecdotal, maintaining a healthy lifestyle is recommended to reduce the incidence of adolescent constipation.